Evaluation of Sola Scriptura in the Perspective of Christian Religious Education and Its Challenges - Majesty, Gilbert Timothy; Litos Sitorus Pane; Juaniva Sidharta (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
The doctrine of Sola Scriptura, which positions Scripture as the supreme authority in matters of faith and practice, has been a foundational pillar for Protestant Christianity. However, its application within the dynamic context of modern Christian Religious Education (CRE) faces significant challenges that necessitate a critical evaluation. This study employs a qualitative research method with a descriptive-analytical approach to comprehensively investigate the interplay between this theological principle and contemporary educational praxis. The research is conducted by systematically gathering and analyzing a wide range of textual sources, including seminal theological works on Sola Scriptura, current CRE curricula, relevant scholarly articles, and educational policy documents. The analysis describes the core tenets of the principle as historically understood, followed by an examination of its practical implementation in educational settings. The study identifies and elucidates key challenges, such as the rise of historical-critical biblical interpretation, increasing religious pluralism, the pervasive influence of secularism, and the pedagogical shift towards student-centered learning models that prioritize personal experience. The findings reveal a critical tension between the exclusive truth claims inherent in Sola Scriptura and the inclusive, relativistic environment of the modern world. The study concludes that for CRE to remain relevant and effective, it must develop thoughtful pedagogical strategies that faithfully uphold the authority of Scripture while simultaneously engaging with these contemporary challenges. This necessitates a move beyond a mere transmission of doctrine towards fostering a critical and reflective faith among learners, enabling them to navigate the complexities of the modern age.